El proceso social de formulacion de la ley forestal de Bolivia de 1996 - Lizarraga, I. P.; Helbingen, A. B. (CIFOR, Centro de Estudios para el Desarrollo Laboral y Agrario, Teller de Iniciativas en Estudios Rurales y Reforma Agraria, Bolivia Sustainable Forest Management Project, 1998)
This work presents, for first time, an opportunity of knowing the process of the formulation of the new Forestry Law in Bolivia, approved in July 1996. The formulation of this law was a long and difficult social process, full of conflicts between the different actors involved and delays. The book shows the politics as it is, with all its alliances of convenience, small tragedies and surprises and the powerful interests behind it, but it also demonstrates that democracy can work and that there are still possibilities to conciliate all these interests in the forestry sector. This study is included in a CIFOR initiative to look at the process of formulation of new forestry laws in Bolivia, Cameron, Costa Rica and Indonesia.